Review Article: Guidelines for the Diagnosis and Management of Gastroesophageal Reflux Disease - Karim, Mohammad Enamul; Rahim, Sayeda; Mahmuduzzaman, Mohammad; Ghosh, Dilip Kumar; Islam, Atiqul; Ahmed, Habib; Rowshon, AHM (Journal of Shaheed Suhrawardy Medical College, 2017)
Gastro Esophageal Reflux Disorders(GERD) are group of conditions where gastric contents are refluxed into the esophagus and produce troublesome symptoms mainly heartburn and regurgitation. It may present with complications as well. Atypical presentation is also not very uncommon. Proper diagnosis and differentiation from other diseases can ensure appropriate treatment and thus better quality of life. Unlike many other diseases, diagnosis of GERD is relatively straight forward through symptomatology and a few investigations, even though few cases require special and technologically newer modalities of investigative tools for confirmation. Option for treatment are many and mostly medical; surgical and other methods are very rarely needed to pose better life. New molecules are recently being used with variable promising results and need exploration. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 30-33